2013
DOI: 10.2190/om.66.1.d
|View full text |Cite
|
Sign up to set email alerts
|

Over My Dead Body: Body Donation and the Rise in Donor Registrations in the Netherlands

Abstract: In The Netherlands, the number of body donor registrations has been increasing for several years. Body donors are people who register at an anatomical institute to donate their entire body, after death, for scientific education and research. Although only 0.1% of the Dutch population is registered as a body donor, this is sufficient to realize the anatomical demand of about 650 bodies annually. Due to the recent rise of registrations many anatomical institutes have (temporarily) stopped registering new donors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…The appearance of this age characteristic (∼60 years of age) among potential donors at the time of registration in various studies is likely due to the fact that it is the age at which many people consider death and the fate of their bodies. These observations are discussed by Bolt et al (/2013), who suggested that the attitude of such elderly people would be in accordance with “gerotranscendence theory” (Tornstam, ). This theory states that, with age, the elderly tend to increasingly consider their relationship and impact on past and future generations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The appearance of this age characteristic (∼60 years of age) among potential donors at the time of registration in various studies is likely due to the fact that it is the age at which many people consider death and the fate of their bodies. These observations are discussed by Bolt et al (/2013), who suggested that the attitude of such elderly people would be in accordance with “gerotranscendence theory” (Tornstam, ). This theory states that, with age, the elderly tend to increasingly consider their relationship and impact on past and future generations.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the predominance of females among donors may be linked to the observation that women happen to be more altruistic than men, and because of this, religious traditions that reward altruism appeal to them more. Also individuals who go to church have more social interactions, are more likely to help others, and are more actively involved in organizations (Bolt et al, /2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the period 2013–2017 the School of Anatomical Sciences at the University of the Witwatersrand has been able to reverse the situation and progressively transition to acquisition of cadavers from bequests and donors in accordance with the ethical principles of donation as set out by TEPARG and the IFAA (McHanwell et al, ; IFAA, ). This transition from unclaimed cadavers to a majority of bequeathed and donated bodies is reflective of the change that has occurred in the acquisition of cadavers at major institutions across the globe (Bolt et al, ; Gangata et al, ; Park et al, ; da Roche et al, ). The reasons for the change at the School of Anatomical Sciences, University of the Witwatersrand may be three‐fold: engagement with relevant populations of individuals by the School/local professional body (ASSA); the “high cost of dying” which has occurred in South Africa over the last number of years; and/or a government subsidy provided to burial companies for the burial of unclaimed bodies.…”
Section: Discussionmentioning
confidence: 99%
“…While the numbers of living individuals who are intending to bequeath their bodies is on the increase as evidenced by the School's database, they have not yet reached the numbers in bequest databases reported at institutions in the Netherlands (Bolt et al, ). The School of Anatomical Sciences at the University of the Witwatersrand is concerned that the numbers of bequests will not be sustained into the future as evidenced by the drop in bequests observed by Wijbenga et al ().…”
Section: Discussionmentioning
confidence: 99%
“…There is also a moral significance surrounding how anatomists use the cadaver (anatomic gift/donor) for dissection activities (Jones, 1994). Most individuals donate their body to science with the hope of advancing the field of medicine (Bolt et al, 2011(Bolt et al, , 2012Cornwall et al, 2012). If the human brains remain under-utilized in academic medicine, then it is possible that educators, who use the anatomic gift for teaching, are not living up to ethical obligations (Biasutto et al, 2014b).…”
Section: Figurementioning
confidence: 99%